An introduction to applying social work theories and methods - Teater, Barbra (Open University Press, 2014)
"A basic introduction to the most commonly used theories and methods in social work practice. The book explores the concept of a theory and a method, the difference between the two and the ways in which they are connected. Teater also discusses the social worker-client relationship and offers a handy overview of anti-oppressive practice"--Back cover.